2022
DOI: 10.3390/plants11020193
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Safety and Efficacy of a Herbal Mixture Used for Contraception by Traditional Health Practitioners in Ngaka Modiri Molema District Municipality, South Africa

Abstract: The use of medicinal plants for contraception remains a common practice among South African ethnic groups. The present study assessed the phytochemical profile, cytotoxicity, acute oral toxicity and efficacy of a herbal mixture used for contraception by the Batswana of South Africa. An aqueous extract was prepared from equal quantities (in terms of weight) of Bulbine frutescens (roots), Helichrysum caespititium (leaves) and Teucrium trifidum (leaves) based on a recipe used by traditional health practitioners. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…In the same vein, [22], who established Azadirachta indica as an effective contraceptive agent, also identified high concentrations of flavonoids and alkaloids in the plant, a clear indication that these phytochemicals may be responsible for the contraceptive efficacy of the tested extract. Furthermore, findings in this study are supported by that of [23] who observed that phenolic compounds are potent contraceptive agents.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the same vein, [22], who established Azadirachta indica as an effective contraceptive agent, also identified high concentrations of flavonoids and alkaloids in the plant, a clear indication that these phytochemicals may be responsible for the contraceptive efficacy of the tested extract. Furthermore, findings in this study are supported by that of [23] who observed that phenolic compounds are potent contraceptive agents.…”
Section: Discussionsupporting
confidence: 88%
“…As supported by the work of [23] who observed no significant weight loss in animals treated with herbal contraceptives, this study showed nonsignificant (p>0.05) alterations in the body weight of rats in groups 2, 3 and 4, when measured before and after the administrations, indicating that the extract had no significant effect on the body mass of the rats administered with a low dose. However, there is a significant decrease in weight of test group 5, which conforms to the findings of [42], who observed a significant decrease in body weights of albino rats administered with Sida acuta extract.…”
Section: Discussionsupporting
confidence: 72%
“…2,9 Herbal contraceptive techniques have been utilized for centuries across various cultures and traditions, and they present numerous advantages over synthetic hormones, intrauterine devices, or surgical interventions. 10 The utilization of this approach is deemed to be less hazardous and milder towards the physiological system, as it refrains from disrupting the inherent hormonal equilibrium or inflicting harm to the reproductive structures as is the case of sterilization. 5 The utilization of this approach is deemed to be less hazardous and milder towards the physiological system, as it refrains from disrupting the inherent hormonal equilibrium or inflicting harm to the reproductive structures as is the case of sterilization.…”
Section: Introductionmentioning
confidence: 99%